Orthodontic treatment of bimaxillary protrusion - A case with extracted maxillary lateral incisor - Suruchi Satyajit Jatol-Tekade; Satyajit Ashok Tekade; Kush Pathak; Sachin Tikekar (Wolters Kluwer Medknow Publications, 2018)
This article is presented for reporting a case of an extracted maxillary lateral incisor before orthodontic treatment planning, and canine substitution was performed as best option remained. This procedure required special consideration for esthetics and functional issues. A 21-year-old female patient with missing upper right lateral incisor with Class I bimaxillary protrusion came to seek treatment for malaligned teeth. Previously, she tried getting them corrected by extracting most prominent tooth which was maxillary right lateral incisor most probably. As she must have strongly requested to the previous dental surgeon about extraction, she got the lateral incisor removed. But to patient's displease, extraction of upper right lateral incisor didn't solve the problem and came to Orthodontist for correction of malaligned teeth. This skeletal Class II patient was having lateral tongue thrust on the right side causing posterior open bite, and on the left side, premolar and molar were in crossbite. Over-retained and malpositioned 53 caused 13 impacted and might have caused 12 to erupt so much labially that it needed to be removed. At the end of treatment, the patient was having Class II molar relation on both sides. The upper right canine was reshaped to look like lateral incisor. Esthetic results were satisfactory to the patient.